2017
DOI: 10.1038/srep39882
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the hydraulic and heat-transfer properties of artificially fractured granite

Abstract: In this paper, the hydraulic and heat-transfer properties of two sets of artificially fractured granite samples are investigated. First, the morphological information is determined using 3D modelling technology. The area ratio is used to describe the roughness of the fracture surface. Second, the hydraulic properties of fractured granite are tested by exposing samples to different confining pressures and temperatures. The results show that the hydraulic properties of the fractures are affected mainly by the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…As it is shown in Equation (1), the hydraulic conductivity is proportional to the aperture and inversely proportional to the kinematic viscosity of fluid. It has been previously reported that water viscosity decreases from 100.5 × 10 −5 to 28.38 × 10 −5 Pa·s when the temperature increases from 20 to 100 • C (25). The viscosity of the water decreases relatively rapidly at a low temperature range, resulting in an increase of hydraulic conductivity.…”
Section: Influence Of Confining Pressurementioning
confidence: 95%
See 1 more Smart Citation
“…As it is shown in Equation (1), the hydraulic conductivity is proportional to the aperture and inversely proportional to the kinematic viscosity of fluid. It has been previously reported that water viscosity decreases from 100.5 × 10 −5 to 28.38 × 10 −5 Pa·s when the temperature increases from 20 to 100 • C (25). The viscosity of the water decreases relatively rapidly at a low temperature range, resulting in an increase of hydraulic conductivity.…”
Section: Influence Of Confining Pressurementioning
confidence: 95%
“…Based on the experimental results, Li proposed heat transfer correlations. Luo et al [25] tested the hydraulic properties of artificial fractured granite under different confining pressure and temperature, then further studied the heat transfer efficiency under coupled hydro-thermal-mechanical conditions. It was found that the hydraulic property depends largely on the surface area of the fractures.…”
Section: Description Of the Samplesmentioning
confidence: 99%
“…Figure 2 shows the physical structure model of heat transfer. Luo et al [35,36] analyzed the heat transfer phenomenon in the flow process, and results showed that heat flow is a process of energy exchange. Therefore, the author divides the heat transfer process into three types: linear, curved, and spiral.…”
Section: Causes Of Formation Of High Ground Temperaturementioning
confidence: 99%
“…Additionally, the response of a rock fracture to THMC processes also depends on the morphology of the fracture surfaces (Pyrak-Nolte and Morris 2000). Size and spatial distribution of mechanical apertures as well as contact areas directly influence the hydraulic characteristics of the fracture, where large mean mechanical apertures and pronounced roughnesses tend to result in higher hydraulic conductivities and larger hydraulic aperture variations when mechanical loads change (Bandis et al 1983;Luo et al 2017). The spatial correlation of fracture aperture fields is also expected to play a significant role in the response of the fracture to increased compressive stresses, as a high spatial correlation results in preferential flow channels.…”
Section: Figmentioning
confidence: 99%